The Effect of Online Frontliner Interpersonal Communication on Consumer Purchase Decisions of Cv Borneo Store Banjarmasin - Putri Pahira, Recka; Lieta Dwi Novianti; Dewi Merdayanty (Universitas Indo Global Mandiri, 2024)
The existence of frontliners has a very viral role in providing services to consumers, because they are the first people faced by consumers when interacting with companies. As a company representative, frontliners function to create a positive first impression through the attitude and service provided. The quality of service shown by the frontliner will greatly affect consumers' perception of the company, which can ultimately affect their purchasing decisions. Therefore, good interpersonal communication from the frontliner is key in creating a satisfying customer experience. This study aims to determine the influence of online frontliner interpersonal communication on purchase decisions in CVs. Borneo Store Banjarmasin. The research method used is a quantitative approach with data collection through questionnaires distributed to consumers who shop at CV. Borneo Store. The research sample is 73 people who are randomly selected using the *simple random sampling* technique. The collected data was then analyzed using a simple linear regression with reference to the AIDDA (Attention, Interest, Desire, Decision, Action) theory, which describes the stages in the consumer decision-making process. The results of the study show that good interpersonal communication from online frontliners has a significant effect on consumer purchase decisions. A simple linear regression test showed that the determination coefficient was 40.1% with a significance level of 0.001 (<0.05), which means that online frontliner interpersonal communication had a considerable influence on the purchase decision. These findings show that effective communication between frontliners and consumers, both in-person and online, is important for building relationships, creating trust, and driving purchasing decisions. Companies need to pay attention to the quality of frontliner communication, especially in the digital era, to increase customer satisfaction and loyalty. Keywords: Online Frontliner, Consumer, Purchase Decision, AIDDA Theory, Simple Linear Regression, Interpersonal Communication